2014
DOI: 10.1159/000363031
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 21 Protects Against High Glucose Induced Cellular Damage and Dysfunction of Endothelial Nitric-Oxide Synthase in Endothelial Cells

Abstract: Aims: Fibroblast growth factor 21 (FGF21) is a powerful endocrine hormone modulating glucose and lipid metabolism and represents a promising drug for type 2 diabetes. The present study was to determine the effect of FGF21 on high glucose-induced damage and dysfunction in endothelial cells. Methods: The protein expression of β-klotho was examined in human umbilical vein endothelial cell (HUVECs) using immunofluorescence and Western blotting. HUVECs were cultured in medium with normal glucose (NG), high glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 72 publications
3
35
1
Order By: Relevance
“…It is known that impaired EDV in obese rats arises from decreased production and/ or bioactivity of NO induced by eNOS phosphorylation [15,27]. In the present study, we found that induction of HO-1 with CoPP significantly enhanced eNOS phosphorylation and total production of NO by thoracic aortic rings compared with that by rings from obese rats without CoPP pre-incubation.…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 58%
“…It is known that impaired EDV in obese rats arises from decreased production and/ or bioactivity of NO induced by eNOS phosphorylation [15,27]. In the present study, we found that induction of HO-1 with CoPP significantly enhanced eNOS phosphorylation and total production of NO by thoracic aortic rings compared with that by rings from obese rats without CoPP pre-incubation.…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 58%
“…While FGF21KO-SED WAT and BAT had a more pro-inflammatory phenotype compared to WT-SED mice, it is unclear if that was a direct effect of FGF21 ablation, or secondary to the increase in adiposity observed in the KO mice. However, emerging data suggest a direct role for FGF21 in alleviating ER stress and inflammation (Guo, et al 2016; Wang, et al 2014; Yu et al 2016). In order to interrogate further whether the inflammatory changes observed in the KO mice were dependent or independent of the increase in adiposity, we statistically adjusted for the effect of body weight on all inflammatory outcomes (Supplementary Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas lean adipose tissue is characterized by the absence of inflammation and increased mitochondrial function (Flachs, et al 2013), obese/sedentary adipose tissue is typified by a pro-inflammatory phenotype and impaired mitochondrial activity (Okamoto, et al 2007). Meanwhile, exercise improves WAT mitochondrial content and function (Stanford et al 2015; Wang et al 2014), and reports have implicated FGF21 in mediating mitochondrial biogenesis via regulation of Pgc1alpha (Okamoto et al 2007; Stanford et al 2015). Thus, mitochondria-related markers were assessed in WAT and BAT to determine the potential impact of loss of FGF21 on the ability of exercise to affect these parameters.…”
Section: Discussionmentioning
confidence: 99%
“…β‐klotho is enriched in the liver, white (WAT) and brown adipose tissues (BAT), the pancreas, and the central nervous system (CNS), which critically modulates glucose and lipid homeostasis. In addition, β‐klotho has been recently detected in other tissues such as placenta, human umbilical vein endothelial cells, and endothelial cells; in which FGF21 has been suggested to regulate the local metabolism in those tissues.…”
Section: Fgf21 Signalingmentioning
confidence: 99%